Ácido giberélico no incremento de tamanho e produção de frutos partenocárpicos de Physalis Peruviana L. - Wisniewski, Danieli (2018)
Físalis draws attention from producers and consumers for the beauty of its fruits that are surrounded by the sepals forming a balloon, being much used in the decoration of sweets among other dishes and in floriculture. The cultivation in protected environment gives the plant greater protection against the sun's rays, but with the low visitation of pollinating insects and little wind circulation in the greenhouse, it makes this environment unfavorable for fertilization and can result in loss of fertility, in these cases if makes use of strategies to increase fruit size and / or produce seedless fruits, such as the use of hormones that already occurs with other fruits. The objective of this study was to evaluate the effect of different doses of 0ppm, 100ppm, 200ppm, 300ppm and 400ppm of gibberellic acid at different stages of pre-anthesis, before and post-anthesis application in fruits with self-pollination and cross- pollination, in the expectation of generating parthenocarpic fruits and promote fruit size increase. The results were submitted to analysis of variance and the means were compared through regression analysis, with 5% significance. The doses of gibberellic acid did not promote parthenocarpic fruits, the pre-anthesis stage promoted the reduction of the number of seeds in both types of pollination, the doses in the anthesis stage generated an increase of the seed mass as the doses increased in both types of pollination in the post-anthesis stage, both the number of seeds and the seed mass decreased according to the increase of the doses in both types of pollination, the interaction between the application of the growth regulator and cross-pollination was significant.